Factors associated with staff perceptions towards inclusive education in Singapore. (15th January 2016) - Poon, Kenneth K.; Ng, Zijia; Wong, Meng Ee; Kaur, Sarinajit
Abstract : In this study, we sought to examine the perceptions of teachers and other school professionals towards the inclusion of secondary school students with special educational needs (SEN), and the associated factors. The Sentiments, Attitudes and Concerns about Inclusive Education Revised scale (SACIE-R) was completed by 131 teachers and school professionals from two mainstream secondary schools in Singapore. The findings revealed an overall neutral attitude towards inclusion. Together, confidence in teaching students with SEN, the level of training SEN support, as well as experience teaching students with SEN account for a large proportion of the variance in ratings of inclusive perceptions. Further analyses revealed that confidence in teaching or supporting students with SEN was found to be a significant predictor of inclusive perceptions. The findings suggest that schools seeking to engage in inclusive practices should focus on ways to develop the confidence of personnel to support students with SEN. Professional development and mentorship were suggested as possible avenues.